2017
DOI: 10.3233/cbm-160058
|View full text |Cite
|
Sign up to set email alerts
|

Pri-miR-34b/c rs4938723 polymorphism increased the risk of prostate cancer

Abstract: The association studies between miR-34b/c rs4938723 polymorphism and cancer risk showed conflicting results. This study aimed to assess the impact of rs4938723 polymorphism on prostate cancer risk. This case-control study was done on 151 prostate cancer (PCa) patients and 152 benign prostate hyperplasia to examine whether rs4938723 polymorphism in the promoter of pri-miR-34b/c was linked to the carcinogenesis of PCa in a sample of Iranian population. Genotyping of Pri-miR-34 b/c rs4938723 polymorphism was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
1
24
2
Order By: Relevance
“…It has been suggested that lncRNA PRNCR1 promotes prostate carcinogenesis via activating AR (26). SNPs, a class of genetic variations, are commonly used in the prediction of cancer risk (38,44,45), prognosis (46) and clinical outcome (47). Cumulative evidence indicates that non-coding genes may be involved in gene expression complexity in humans (48,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that lncRNA PRNCR1 promotes prostate carcinogenesis via activating AR (26). SNPs, a class of genetic variations, are commonly used in the prediction of cancer risk (38,44,45), prognosis (46) and clinical outcome (47). Cumulative evidence indicates that non-coding genes may be involved in gene expression complexity in humans (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 358 subjects participated in this hospital-based case-control study, including 178 unrelated men with histopathologically confirmed prostate cancer and 180 age-matched unrelated men with benign prostatic hyperplasia (BPH), with no history of any type of cancer, as the control group (36)(37)(38)(39). All cases and controls were selected from a university-affiliated referral center (Shahid Labbafinejad Medical Center, Shahid Beheshti University of Medical Sciences, Tehran, Iran).…”
Section: Methodsmentioning
confidence: 99%
“…Growing evidence has indicated that mutation or polymorphisms in miR genes could affect target-binding activity, expression or processes of mature miR, consequently affecting the expression of their target genes (15,16). Polymorphisms in miR have been demonstrated to be associated with the development of PCa (17,18,31,32). In present study, it was hypothesized that the 3-bp indel polymorphism of pre-miR-3131 may be associated with the development of PCa.…”
Section: Discussionmentioning
confidence: 80%
“…Mounting evidence has suggested that mutation or SNPs in miR genes may affect target-binding activity, expression, or processes of mature miR, thus affecting the expression of their target genes (15,16). Polymorphisms in mature and/or pre-miR sequences may affect miR biogenesis and be associated with the development of various types of cancer (17)(18)(19)(20)(21). Small insertions and deletion (indels) polymorphisms are one of the most common genetic alterations in the human genome that influence human traits and diseases (22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation